A distributed subcortical circuit linked to instrumental information-seeking about threat - Hailey A. Trier; Nima Khalighinejad; Sorcha Hamilton; Caroline Harbison; Luke Priestley; Mark Laubach; Miriam Klein-Flügge; Jacqueline Scholl; Matthew F. S. Rushworth (Proceedings of the National Academy of Sciences, 2025)
Daily life for humans and other animals requires switching between periods of threat- and reward-oriented behavior. We investigated neural activity associated with spontaneous switching, in a naturalistic task, between foraging for rewards and seeking information about potential threats with 7T fMRI in healthy humans. Switching was driven by estimates of likelihood of threat and reward. Both tracking of threat and switching to a vigilant mode in which people sought more information about potential threats were associated with specific but distributed patterns of activity spanning habenula, dorsal raphe nucleus (DRN), anterior cingulate cortex, and anterior insula cortex. Different aspects of the distributed activity patterns were linked to monitoring the threat level, seeking information about the threat, and actual threat detection. A distinct pattern of activity in the same circuit and elsewhere occurred during returns to reward-oriented behavior. Individual variation in DRN activity reflected individual variation in the seeking of information about threats.